Rancang Bangun Model Uji Kapal General Cargo 8202 DWT untuk Pengujian Hidrostatis - Yuni Ari Wibowo; Lulut Alfaris; Anas Noor Firdaus; Nunik Wijayanti (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The development of Indonesia's maritime industry cannot be separated from the growth of sea transportation facilities, in this case, namely the growth of the fleet of ships. However, despite this growth, ship accidents are still a crucial issue. One of the causes is sinking caused by poor ship stability. Transfer of cargo on board from loading-unloading activities causes changes in the stability of the ship. In general, ship stability can be analyzed using a numerical approach with hydrostatic analysis, but to accommodate non-linear behavior, model-test experiments are needed. This research focuses on the design of the model test of the General Cargo 8202 DWT ship. The model-test was made with a 1:60 scale which has a model length (L) of 1.80m, breadth (B) of 0.3m, height (D) of 0.23m and a draft (T) of 0.12m. The model-test is designed by modeling the linesplane and then compiling it into a 3D model. Each station on the ship is patterned on wood, cut and arranged to form a ship pattern, then covered with multiplex and fiber. The design procedure for the model-test made refers to the International Towing Tank Conference (ITTC) standard. Pond testing was carried out to identify the draft and inclination of the ship at 3 loading conditions: lightweight, ballasted load and full load. Based on the test results, the model-test’s draft was in accordance with the principal dimensions and the inclination tended to be stable.